FACTORS INFLUENCING CUSTOMER SATISFACTION OF SOLUSI LAUNDRY BEKASI - Pamungkas, Brian Putra; Sukresna, I Made (Faculty of Economics and Business Diponegoro University, 2020)
This study aimed to see the effect of service quality, perceived value, brand image and promotion to customer satisfaction with customization as the moderating variable for service quality and customer satisfaction in Solusi Laundry. Service quality is one of the most important things for service based business in order to survive. Perceived value is the trade-off between perceived benefits and perceived sacrifice, if customer do not get the benefit equal to the cost paid then customer will be dissatisfied. Brand image is the overall perception of the product or brand formed from information and past experience of the product or a brand, a strong brand image can provide the main advantages for the company one of which can create competitive advantage. The main purpose of promotion is to inform, persuade, and remind consumers of a product or service. Customization will delight the customer because of the individualized attention and solutions which make them feel special and the customer will feel satisfied. This study emphasized that the higher and better the service quality, the better the perceived value, the better the brand image, and the better the promotion will increase the satisfaction of Solusi Laundry customer. This study also found that customization moderates the relationship between service quality and customer satisfaction. The number of samples were 150 customers of Solusi Laundry taken by purposive sampling method. The analytical method of this study uses MRA (Moderated Regression Analysis) and PROCESS analysis by AF Hayes with the SPSS 25 program which previously passed the classic assumption test.